The Green Architecture Approach to Natural School at Suburb - Samosir S.N; Harsidani D.D (International Journal of Architecture and Urbanism, 2019)
Natural school is an educational institution that can answer the environmental problems and rigid education system problems with natural nuances. The green architecture approach is used as a design approach to achieve natural school goals that provide an understanding of how awareness of nature is applied in the school. The green architectural approach can be applied by the use of environmentally friendly local materials, natural ventilation, environmentally friendly waste management, and the use of the minimum natural resource. This study uses a glass box and a black box design method. The result of this study is a natural school design that is environmentally friendly and healthy in the suburb of Medan, Indonesia.